Sistem Informasi Penjualan dan Manajemen Inventory berbasis Web pada Toko Frozen Food Pangan Sehat - Eka Maha Putra Sembiring; Hari Purwanto; Alcianno G. Gani (Jurnal Mahasiswa Informatika dan Desain, 2025)
The rapid development of technology today meets human needs for convenience, speed, and accuracy in obtaining information. Efforts must be made to continually improve the quality and quantity of information technology. A significant advancement in the field of technology is the sales information system, which helps business operators manage their activities more effectively, particularly in handling sales and inventory management through computerization. However, many stores still conduct their sales transactions and inventory management manually and are not yet computerized. For example, the sales and inventory management at Pangan Sehat Frozen Food Store is still done manually. To address this issue, a study was conducted to help the store automate its transaction processes and inventory management through a web-based system, making the processes more accurate, effective, and efficient. Indirectly, this research will provide a more pleasant shopping experience for consumers by shortening their shopping time. The study recommends that stores still using manual processes implement computerization in their operations.